Réponses

Meilleure réponse !
2014-04-18T11:40:06+02:00
Bonjour,

a) (2x + 5)(x + 1) - (2x + 5)(2x - 1) = 0
(2x + 5) [(x + 1) - (2x - 1)] = 0
(2x + 5) (x + 1 - 2x + 1) = 0
(2x + 5) (-x + 2) = 0
2x + 5 = 0   ou  -x + 2 = 0
2x = -5  ou  -x = -2
x = -5/2  ou  x = 2
x = -2,5  ou  x = 2

S = {-2,5 ; 2}

b) x(-x + 4) - 2x(2x + 3) = 0
x [(-x + 4) - 2(2x + 3)] = 0
x (-x + 4 - 4x  - 6) = 0
x (-5x - 2) = 0
x = 0   ou   -5x - 2 = 0
x = 0   ou   -5x = 2
x = 0   ou   x = 2/(-5)
x = 0   ou   x = -0,4

S = {0 ; -0,4}

c) développer les 2 expressions

(2x + 5)(x + 1) - (2x + 5)(2x - 1) 
= (2x² + 2x + 5x + 5) - (4x² - 2x + 10x - 5)
= 2x² + 2x + 5x + 5 - 4x² + 2x - 10x + 5
= -2x² - x + 10

x(-x + 4) - 2x(2x + 3)
= -x² + 4x - 4x² - 6x 
= -5x² - 2x